PENERAPAN MODEL UTAUT DALAM PENGGUNAAN APLIKASI TRANSPORTASI OJEK ONLINE - julinar, marito; Saut Pintubipar Saragih, S.Kom., M.MSI. (Computer Science and Industrial Engineering, 2023)
Existence of online transportation provider that can be used by the community is diverse, but there are still many people who have not used this application-based online transportation service. The problem that arises among users or the public is how online transportation services are perceived by the community, technological developments and also competition for services carried out by service providers has led to different views on user satisfaction with services. In this study, the regression method will be used using the UTAUT model to examine how the actual influence of the variables owned by the community on people's interest in using application-based transportation. Testing the data to be used in this study using SPSS software where this research method uses the regression method. The research steps prior to the simple and multiple linear regression testing were carried out by testing the classical assumptions and also testing the validity and reliability of the respondent's data. In the end, hypothesis testing was carried out by producing several research results, namely all variables in UTAUT generate positive result and positive effect on attitude variable for community partially and simultaneously also all independent variables resulted positive and significant on the attitude of intention in using the application in community. Keywords: online transportation; mobile application; UTAUT